Respuesta :
Answer:
6
Step-by-step explanation:
yoy would subtract the 6x by the 4x getting -2x+10= -2. then you would subtract the 10 from the -2 and get -2x=-12. last divide the -2 by -12 giving you positive 6
4x+10=6x-2
Combine the like terms “4x” and “6x”
So, it’s “4x-6x=-2-10”
-2x=-12
Make it positive (when two negatives, it’s the same as positive in an equation)
x=6
Combine the like terms “4x” and “6x”
So, it’s “4x-6x=-2-10”
-2x=-12
Make it positive (when two negatives, it’s the same as positive in an equation)
x=6